Research Priorities from Animal Behaviour for Maximising Conservation Progress. (December 2016) - Greggor, Alison L.; Berger-Tal, Oded; Blumstein, Daniel T.; Angeloni, Lisa; Bessa-Gomes, Carmen; Blackwell, Bradley F.; St Clair, Colleen Cassady; Crooks, Kevin; de Silva, Shermin; Fernández-Juricic, Esteban; Goldenberg, Shifra Z.; Mesnick, Sarah L.; et al.
Abstract : Poor communication between academic researchers and wildlife managers limits conservation progress and innovation. As a result, input from overlapping fields, such as animal behaviour, is underused in conservation management despite its demonstrated utility as a conservation tool and countless papers advocating its use. Communication and collaboration across these two disciplines are unlikely to improve without clearly identified management needs and demonstrable impacts of behavioural-based conservation management. To facilitate this process, a team of wildlife managers and animal behaviour researchers conducted a research prioritisation exercise, identifying 50 key questions that have great potential to resolve critical conservation and management problems. The resulting agenda highlights the diversity and extent of advances that both fields could achieve through collaboration. Trends: Conservation progress relies on communication between researchers and managers. Ethologists and wildlife managers determined 50 conservation research priorities. The list shows tremendous breadth and potential for conservation gain. We identify routes for developing efficient and cost-effective interventions.